Effect of Gyrinops Versteegii’s Aromatherapy on Work Endurance in First-Year Medical Students - Rianto, Chintya Rosalina Allodya; Prasetya, Era Catur; Akil, Syafarinah Nurhidayah; Primadina, Nova (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
The first year of college is a difficult time for new students. New students are required to have good endurance because it is one of the important factors that must be possessed by individuals to adapt well. Agarwood is known for its fragrant aroma, so it is widely used in aromatherapy. Special compounds contained in agarwood essential oil have a relaxing effect that can reduce fatigue levels. This study aims to examine the effect of Gyrinops versteegii essential oil aromatherapy on the work endurance in first-year students at the Faculty of Medicine, University of Muhammadiyah Surabaya. An experimental crossover design involving 32 first-year students. Data was collected through Inhalation of Gyrinops versteegii essential oil vapor from a diffuser, vital sign measurement, and Kraepelin test results. The data obtained will be processed using SPSS version 27 for Windows. Wilcoxon test results showed a significant difference in work endurance (p = 0.025). Kendall's Tau-b correlation test revealed a non-significant and weak correlation between work endurance (p = 0.071; r = 0.284). In conclusion, aromatherapy with Gyrinops versteegii essential oil has an impact on work endurance, with a significant decrease in work endurance in first-year medical students.